Influence of body odors and gender on perceived genital arousal - Alves-Oliveira, P. (2018)
Olfaction is often linked to mating behavior in nonhumans. Additionally, studies in mating behavior have shown that women seem to be more affected by odor cues than men. However, the relationship between odor cues and sexual response—specifically, sexual arousal—has not been studied yet. The aim of this study was to evaluate the impact of the exposure to human body odors (from individuals of the opposite gender) on perceived genital arousal, while these were presented concomitantly to sexually explicit video clips. Eighty university students (40 women) rated their perceived genital arousal (perceived degree of erection/genital lubrication) in response to an audiovisual sexual stimulus, while simultaneously exposed to a body odor from an opposite-gender donor or no odor. Participants also rated each odor sample’s (body odor and no odor) perceived pleasantness, intensity, and familiarity. Findings indicated that odor condition had an effect on women’s (but not men’s) perceived genital arousal, with women showing higher levels of perceived genital arousal in the no odor condition. Also, results showed that women rated body odors as less pleasant than no odor. Notwithstanding, the odor ratings do not seem to explain the association between body odor and perceived genital arousal. The current results support the hypothesis that women, rather than men, are sensitive to odors in the context of sexual response. The findings of this study have relevance for the understanding of human sexuality with respect to chemosensory communication